Relationship between depressive symptoms and cumulative 24-hour urinary norepinephrine excretion level among undergraduate medical students in Uganda - Owoola-Ajirotutu, Mutiat O; Okpanachi, Alfred O; Owoola, Akeem G; Rukundo, Godfrey Zari; Yusuf, Sadiq (bioRxiv, 2019)
Background: Depression is a serious mental health problem in different parts of the world and has been reported to be rising among undergraduate medical students. The incidence of depression has not only been linked to psychosocial factors but also to biological factors, such as altered urinary levels of norepinephrine. This study was carried out to determine the prevalence of depression among undergraduate medical students in Uganda and examine the relationship between depressive symptoms and 24-hour urinary norepinephrine excretion levels in the participants. Methods: One hundred and sixteen undergraduate medical students (75 males and 41 females) of Kampala International University, in southwestern Uganda were evaluated for depression using the 21-item Beck Depression Inventory-II (BDI) questionnaire. Twenty-four-hour urine collections from each participant were assayed for norepinephrine excretion levels. Descriptive statistics and Pearson correlation coefficient were computed to examine the data obtained. Results: The results of this study showed that, a total of 33 participants (28.4%) have depressive symptoms. Students with depressive symptoms had higher but not significant 24-hour urinary mean norepinephrine excretion levels than those without depressive symptoms (121.97±51.48μg/day Vs 87.58±18.64 μg/day, P>0.05). There was a positive weak relationship between BDI scores and 24- hour urinary norepinephrine levels (r= 0.21, p = 0.28). Regression models accounting for socio- demographic characteristics indicated that, type of accommodation, marital status, relationship with parents, educational sponsorship may be risk factors for depressive symptoms observed in the participants. Conclusions: These results suggest that increased urinary norepinephrine excretion and other psychosocial factors may be associated with depressive symptoms. Measurements of 24-hour urinary norepinephrine excretion may serve as an integrative parameter in diagnosing and management of patients with depression.
Keywords: Depression; Mental health; Undergraduate; Psychosocial factors; Uganda